1999
DOI: 10.1121/1.424554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temporal position, proportional variance, and proportional duration on decision weights in temporal pattern discrimination

Abstract: Two experiments investigated how listeners allocate their attention to different segments of a temporal pattern. The experiments allowed a direct test of the predictions of the Proportion of Total Duration (PTD) rule and the Component Relative Entropy (CoRE) model. Listeners had to decide whether two sequences of nine tones had the same or different temporal patterns (tone duration = 25 ms, tone frequency = 1000 Hz). A sequence's temporal pattern was determined by the time intervals between each tone's offset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The analysis consisted of drawing influence curves that show the contribution of each element to the ultimate decision and thereby measure changes in memory of items with time. The technique is similar to that employed by Sadralodabai and Sorkin (1999) to study the influence of temporal position in an auditory stream on decision weights in pattern discrimination. The first experiment gathered a baseline, the second varied the ISI, and the third varied the ITI.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis consisted of drawing influence curves that show the contribution of each element to the ultimate decision and thereby measure changes in memory of items with time. The technique is similar to that employed by Sadralodabai and Sorkin (1999) to study the influence of temporal position in an auditory stream on decision weights in pattern discrimination. The first experiment gathered a baseline, the second varied the ISI, and the third varied the ITI.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, when there was variability in the temporal envelope, the context mode was dominant. Sadralodabai and Sorkin (1999) showed that increases in the average duration of a gap in a tonal sequence have little effect on the attentional weight given to a particular tone, whereas an increase in the variance of the duration of the gap results in greater weight being applied to that tone. They explain this result using Lutfi's (1993Lutfi's ( , 1995Lutfi & Doherty, 1994) component-relativeentropy (CoRE) rule, which suggests that the critical factor in predicting discrimination is a component's relative contribution to the overall variance across all of the patterns in the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular psychophysics is an approach to this problem that focuses on the observer's decision process as it is reflected in the trial-by-trial data ͑Ahumada and Lovell, 1970;Gilkey and Robinson, 1986;Green, 1964;Watson, 1962͒. The approach has gained increasing application in recent years, particularly in studies of multitone pattern discrimination where the relative reliance or decision weight listeners give to the different tones in the stimulus is judged to be an important factor underlying performance ͑Alexander and Lutfi, 2004;Berg, 1989Berg, , 2004Berg and Green, 1990;Dai and Berg, 1992;Lutfi, 1996, 1999;Green and Berg, 1991;Lutfi, 1989Lentz and Leek, 2002;Sadralodabai and Sorkin, 1999;Stellmack and Viemeister, 2000;Stellmack, Willihnganz, Wightman, and Lutfi, 1997;Willihnganz, Stellmack, Lutfi, and Wightman, 1997͒. The techniques for estimating the weights differ in detail in these studies but are derived from the same general model taken to represent different stages of auditory processing leading to a decision ͑cf. Ahumada and Lovell, 1970;Berg, 1989Lutfi, 1989Lutfi, , 1995Richards and Zhu, 1994͒.…”
Section: Introductionmentioning
confidence: 98%